Habituation of Character Values Through the Implementation of Second Precept of Pancasila at MTsN 4 Buton Tengah - Putra, Zulfikar; Arifin, Muhammad; Nurtina, Nurtina (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
This article aims to examine the efforts made by teachers to foster student awareness through the implementation of the second principle of Pancasila at MTsN 4 Buton Tengah. A qualitative case study method was employed, with informants including the principal, Pancasila and Civic Education teacher, and students at MTsN 4 Buton Tengah. The results indicate that teachers foster awareness through various habituation practices: students help their peers in need, students are given responsibilities to maintain classroom cleanliness, mutual respect is cultivated through the 5S principles (smile, greet, salute, politeness, and courtesy), honesty is promoted via an honesty canteen, and discipline is enforced by ensuring students arrive at school on time with sanctions for tardiness. This study is limited by its focus on the second principle of Pancasila. Future research should explore the implementation of other Pancasila principles at the junior high school level.